THE ROLE OF WOMEN IN GLOBAL PEACEKEEPING MISSIONS: UNSC RESOLUTION 2538 - Diana, Dianatul Ilmi; Ronia Pratiwi, Fanisa Ira; Hidayatullah, Achmad Diny (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This research aims to analyze the role of women in peacekeeping missions and the implementation of UNSC Resolution 2538. This study employs a literature review. The role of women in UN Security Council Resolution 2538 (2020) is analyzed using references from academic journals, official websites, and electronic news. The results show that women can help facilitate peace talks more effectively. Women's participation in peacekeeping missions plays an important role in creating global peace. They bring mediation skills, help achieve more durable peace agreements, and provide a sense of security for local populations. Despite challenges, support from governments, NGOs and civil society is needed to increase the role of women. UN Security Council Resolution 2538 of 2020 provides equal opportunities for men and women in peace and conflict missions. This shows that women have a significant role in maintaining global peace, and Indonesia plays an important role in elevating women in maintaining UN welfare and encouraging women's participation in UN environmental missions. The UNSC Resolution on Women in Peacekeeping is also a milestone in Indonesian diplomacy. UNSC Resolution 2538 was initiated by Indonesia and approved by 97 UN countries. Abstrak. Penelitian ini bertujuan untuk menganalisis peran perempuan dalam misi pemeliharaan perdamaian dan implementasi Resolusi UNSC 2538. Studi ini menggunakan tinjauan pustaka. Peran perempuan dalam Resolusi Dewan Keamanan PBB 2538 (2020) dianalisis dengan menggunakan referensi dari jurnal akademis, situs web resmi, dan berita elektronik. Hasil penelitian menunjukkan bahwa perempuan dapat membantu memfasilitasi pembicaraan perdamaian dengan lebih efektif. Partisipasi perempuan dalam misi pemeliharaan perdamaian memainkan peran penting dalam menciptakan perdamaian global. Mereka membawa keterampilan mediasi, membantu mencapai perjanjian perdamaian yang lebih tahan lama, dan memberikan rasa keamanan bagi penduduk setempat. Meskipun menghadapi tantangan, dukungan dari pemerintah, LSM, dan masyarakat sipil diperlukan untuk meningkatkan peran perempuan. Resolusi Dewan Keamanan PBB 2538 tahun 2020 memberikan kesempatan yang sama bagi pria dan wanita dalam misi perdamaian dan konflik. Hal ini menunjukkan bahwa perempuan memiliki peran yang signifikan dalam menjaga perdamaian global, dan Indonesia memainkan peran penting dalam meningkatkan peran perempuan dalam menjaga kesejahteraan PBB serta mendorong partisipasi perempuan dalam misi lingkungan PBB. Resolusi Dewan Keamanan PBB tentang Perempuan dalam Pemeliharaan Perdamaian juga merupakan tonggak dalam diplomasi Indonesia. Resolusi UNSC 2538 diinisiasi oleh Indonesia dan disetujui oleh 97 negara anggota PBB.